The γ-Adducin 1–357 fragment promotes tau pathology - Yu, Honglu; Xiong, Min; Liu, Congcong; Xia, Danhao; Meng, Lanxia; Zhang, Zhentao (Frontiers in Aging Neuroscience, 2023)
Background Tau phosphorylation is a pathological hallmark of Alzheimer’s disease (AD). Previously, we reported that the γ-adducin 1–357 fragment is present in the brains of AD patients. However, it remains unknown how γ-adducin regulates tau phosphorylation. Objective The aim of this project is to investigate the effects of the γ-adducin 1–357 fragment on tau phosphorylation and the kinases involved in this process. Methods Full-length γ-adducin or the γ-adducin 1–357 fragment was expressed in HEK293 cells, SH-SY5Y cells, and primary neurons. The phosphorylation of tau Ser396 was determined using Western blot and immunofluorescence. Tau P301S transgenic mice were injected with adeno-associated virus encoding full-length γ-adducin or γ-adducin 1–357 fragment to determine the phosphorylation of tau. Results The γ-adducin 1–357 fragment enhances tau phosphorylation at Ser396. Additionally, the expression of the γ-adducin 1–357 fragment leads to the activation of glycogen synthase kinase-3β (GSK-3β). This effect was mitigated by the GSK-3β inhibitor 4-Benzyl-2-methyl-1,2,4-thiadiazolidine-3,5-dione (TDZD-8). Conclusion The γ-adducin 1–357 fragment enhances tau phosphorylation by activating GSK3β. These results support that the fragmentation of γ-adducin may play a pivotal role in tau pathology.